Antioxidant Capacity, Cytoprotection, and Healing Actions of the Leaf Aqueous Extract of Ocimum suave in Rats Subjected to Chronic and Cold-Restraint Stress Ulcers. (31st March 2013) - Tan, Paul V.; Mezui, C.; Enow-Orock, G. E.; Agbor, G.
Abstract : We evaluated the qualitative chemical composition and tested the antiulcer actions on cold/restraint stress ulcers, the healing effect on chronic acetic acid-induced gastric ulcers, and the in vivo and in vitro antioxidant capacity of Ocimum suave extract. Triterpenes, flavonoids, sugars, phenols, sterols, and multiple bonds were among the phytochemicals detected. The extract (250–500 mg/kg) dose-dependently inhibited the formation of gastric ulcers induced by cold/restraint stress (52.30%–83.10%). The prophylactic actions were associated with significant increases in gastric mucus production. There was significant histological healing of chronic ulcers following 14-day treatment with O. suave extract (250–500 mg/kg). We also evaluated the efficacy of O. suave extract in cold/restraint-induced oxidative stress in rat stomach tissue. O. suave (500 mg/kg) ameliorated the decreased levels of reduced glutathione from 0.85 (control group) to 2.08 nmol/g tissue. The levels of SOD and catalase were also improved in rats treated with O. suave extract. The extract had a high phenol content (899.87 mg phenol/g catechin equivalent), in vitro DPPH radical scavenging activity (89.29%), and FRAP (antioxidant capacity) (212.64 mg/g catechin equivalent). The cytoprotective and ulcer healing effects of the extract are attributed to enhanced mucus production and the antioxidant properties which may likely be associated with the high presence of flavonoids and polyphenols.